Phytoplankton Diversity and The Potential of Harmful Algal Blooms (HABs) in Utan Waters Sumbawa - Supriatna, Nunung; Buhari, Nurliah; Jefri, Edwin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Phytoplankton serve as primary producers and bioindicators in aquatic ecosystems. Elevated nutrient concentrations can trigger excessive phytoplankton proliferation, resulting in Harmful Algal Blooms (HABs) that adversely affect aquatic organisms. This study evaluated phytoplankton diversity and the potential for HAB formation in Utan Waters, Sumbawa. Water samples were collected from three purposively selected stations and analyzed in the laboratory to identify phytoplankton genera and calculate ecological indices, including diversity, evenness, dominance, and abundance. Concurrent in situ measurements of temperature, salinity, and current velocity were conducted. A total of twelve genera across four classes were identified, with Oscillatoria (Cyanophyceae) exhibiting the highest abundance. The diversity index ranged from moderate values (H’ = 1.29–1.64), evenness varied from low to moderate (E = 0.54–0.71), and dominance was high (D = 1.93–2.00). Potentially harmful genera detected included Oscillatoria, Ceratium, Chaetoceros, Coscinodiscus, and Rhizosolenia; however, their abundances remained below established HAB thresholds, indicating no current bloom events. The presence of these genera suggests that environmental conditions may support HAB development in the future. Therefore, regular monitoring and nutrient analyses (nitrate, phosphate, chlorophyll-a) are recommended for early detection and sustainable ecosystem management.